INTEGRASI NILAI-NILAI KEISLAMAN DAN NILAI-NILAI KEBANGSAAN PADA PONDOK PESANTREN DARUSSALAM MARTAPURA, PONDOK PESANTREN AL FALAH LANDASAN ULIN BANJARBARU DAN PONDOK PESANTREN DARUL HIJRAH CINDAI ALUS BANJARBARU - Insyirah Insyirah (PROCEEDING UMSURABAYA, 2022)
This study aims to explore how to integrate Islamic values and national values at the Darussalam Islamic Boarding School Martapura, Al Falah Islamic Boarding School Platform Ulin Banjarbaru and Darul Hijrah Islamic Boarding School Cindai Alus Banjarbaru. This study uses a type of field research (field research) and uses a qualitative approach with data described descriptively. Data collection techniques using observation, interviews and documentation. The data analysis technique uses data reduction techniques, data display and data verification. The results of this study can be seen that the integration of Islamic values and national values is through the curriculum, through learning materials and processes, integration through competitions to commemorate Indonesian Independence Day and extracurricular activities. The curriculum consists of two curricula, namely the cottage curriculum and the State curriculum, this proves that there is an integration of the two values. In the cottage curriculum, maximum religious values are instilled and the country's curriculum is involved in the service, then the values of nationalism are automatically instilled. Activities outside or in the field are holding activities on August 17, a national day, there are commemorations on August 17 and that is the forerunner to be repeated every year. Meanwhile, extracurricular activities are scout activities and PMR.Â Keywords: Integration; Islamic Values; National Value, Islamic Boarding School